Direct visualization of the reaction transformation and signal amplification in a DNA molecular machine with total internal reflection fluorescence microscopy - Ren, Rui; Wang, Haiyan; Liu, Rui; Zhang, Shusheng (Frontiers in Chemistry, 2013)
In this study, as a proof of concept, the signal amplification in an artificial DNA molecular machine was directly visualized via total internal reflection fluorescence microscopy (TIRFM). The molecular machine brought about obvious morphology change in DNA nanostructures as well as signal amplifications. On one hand, through a triggered and autonomically repeated RCA, a DNA nano-complex featuring a “locked” circular DNA template (serving as raw feed) was converted into a long periodically repeated strand, i.e. the RCA products. Furthermore, this RCA was repeated in three controllable reaction phases, bring about progressive signal amplification. It was testified that the RCA products (presented as long thread-like fluorescent objects) can be easily distinguished from the inputted DNA probes (presented as fluorescent dots), thus the transformation in reaction can be visualized. Also, by quantitive counting of the aforementioned fluorescence objects, the progress of the reaction through the phases, along with time, and over the lysozyme concentration can be demonstrated through TIRFM visualization. Overall, it was demonstrated that TIRFM is an efficient approach to quantitively visualize the biochemical processes at single-molecule level.